Mocca survey data base I: Dissolution of tidally filling star clusters harbouring black hole subsystems - Giersz, Mirek; Spurzem, Rainer (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We investigate the dissolution process for dynamically evolving star clusters embedded in an external tidal field by exploring the mocca survey data